Angkutan Sedimen Total Saluran Pembawa Embung Rawasari menggunakan Metode Empiris dan Software HEC-RAS 6.0 - Aswar Amiruddin; Refina Fatriza; Rahmat Faizal (Borneo Engineering : Jurnal Teknik Sipil, 2023)
The need for water will continue to increase, while the availability of water is limited; therefore, the provision of water must be pursued both by the government and independently. Rawasari Reservoir is one of the reservoirs in Tarakan City with a relatively stable volume and an effective storage capacity of 112,982 m3. The water source of Rawasari Reservoir comes from a channel that is a tributary experiencing sedimentation due to the sedimentation process. Based on this, the research team was interested in calculating sediment transport in the conveyance channel of Rawasari Reservoir using both empirical methods and the HEC-RAS 6.0 software. The methods used in this research are empirical using the Engelund Hansen and Laursen equations, as well as the use of HEC-RAS 6.0 software. Based on the analysis results, the sediment transport rate in the conveyance channel of Rawasari Reservoir calculated using the empirical method at STA 0+025 is 1,6427 x 10-9 ton/s for the Engelund Hansen method and 2,9898 x 10-9 ton/s for the Laursen method. The simulation of sediment transport in the bed of the conveyance channel of Rawasari Reservoir using the HEC-RAS 6.0 sediment transport model at STA 0+025 is 4,61x10-5 ton/s with the Engelund Hansen sediment transport function and 0,000306 ton/s using the Laursen sediment transport function.